Latent Variable Models for Longitudinal Outcomes from a Parenting Intervention Study - Mccready, Carlyle (Department of Statistical Sciences, 2020)
This research project analysed data collected with the use of self-reporting questionnaires and observational video scores in order to determine the level of success achieved by the Sinovuyo Caring Families Programme (SCFP). The SCFP aimed to reduce harsh parenting practices and child behavioural problems in high-risk South African families. This research project examined the use of structural equation modelling (SEM) for longitudinal profiles and latent growth mediation modelling. Improved behaviour was observed in terms of reported child behaviour problems and reported harsh parenting with differences between the intervention and control groups directly after the completion of the 3-month intervention program. Improved behaviour was also observed in terms of reported positive parenting with differences between the intervention and control groups directly after the completion of the 3- month intervention program and at the 12-month follow-up occasion. No improvement in observed child behaviour was mediated through reported positive parenting or reported harsh parenting. Furthermore, the intervention program led to improved positive parenting behaviour directly after the 3-month intervention period, however the improved behaviour of the parent did not act as a mediating variable and no improvement in child behaviour was observed as a result.